Agile ramp-up production as an advantage of highly iterative product development. (January 2021) - Bergs, Thomas; Apelt, Sebastian; Beckers, Alexander; Barth, Sebastian
Abstract: Current ramp-up productions at manufacturing companies are characterized by a high quantity of unpredicted development efforts. These unpredicted development efforts result in not achieved ramp-up targets such as time-to-market or time-to-volume and in exceeded ramp-up budgets. The highly iterative product development offers the potential to reduce unpredicted development efforts due to the agile approach and the manufacturing of a high quantity of physical prototypes. In the following, agile ramp-up production as the combination of highly iterative product development and ramp-up production is presented as a potential solution approach to optimize and stabilize current ramp-up productions by reducing unpredicted development efforts.